Irritable Bowel Syndrome Diagnosis: Should There Be Alertness to Cancer? - A. A. Sheptulin; N. L. Jahaya; A. V. Sedova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2019)
Aim. To justify the need to include colorectal cancer (CRC) in the circle of differential diagnostic search for suspected irritable bowel syndrome (IBS).Background. In accordance with the latest Rome IV criteria for IBS, its diagnosis is mainly based on the assessment of clinical symptoms and objective examination data with a very limited list of additional studies. In this case, colonoscopy for suspected IBS is performed only in patients aged over 50 years old, provided a hereditary predisposition to CRC and the “alarm symptoms” are detected. It has been recently shown that CRC can proceed under the “mask” of IBS. However, colorectal and rectal tumours are often found in patients younger than 50 years old in the absence of hereditary predisposition to CRC and “anxiety symptoms”. This makes it necessary to conduct colonoscopy for all patients with suspected IBS.Conclusion. The list of diseases requiring differential diagnostics in patients with suspected IBS should always include CRC.